LINGUALIZATION OF THE IMAGE OF THE WIFE IN THE WORKS OF VASYL STEFANIK - Brus, Maria (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2023)
The article characterizes the category of femininity as a fragment of the study of the linguistic picture of the world and the conceptual picture of the world, which have become key concepts of modern cognitive linguistics. The object of the research is the common names of female persons, which express the status of the wife in the Ukrainian language and reflect many ancient and current processes of linguisticization of the image of the wife. The work of the Ukrainian writer Vasyl Stefanyk is taken as a source - a representative of the Western Ukrainian variant of the literary language and the Pokut dialect of the southwestern dialect, where archaic and modern linguistic means are largely localized and diversified, and in particular those related to the expression of the image of a wife. In the lexical dimension, this is a certain number of semantic units that have been established since ancient times in the Ukrainian language and have been preserved mainly in dialect speech. But their reproduction makes it possible to understand the picture of the formation of nobility and ideas in the Ukrainian conceptual picture of the world of the image of a woman in relation to her husband, as well as to learn the means and methods of its embodiment in the Ukrainian linguistic picture of the world.